The physical universe - Krauskopt, Konrad Bates (McGraw-Hill, 1997)
The book presents the essentials of physics, chemistry, earth science, and astronomy. The first concern in this book is the scientific method, using as illustration the steps that let today's picture of the universe and the earth's place in it. Next the book considers motion and the influences that effect moving bodies. Gravity, energy, and momentum are examined and the theory of relativity is introduced. The book draws the matter in its three states from the kinetic-molecular model to the laws of thermodynamics and the significance of entropy. A grounding in electricity and magnetism follows, and then an exploration of wave phenomena that includes the electromagnetic theory and light. The book goes on from there to the atomic nucleus and elementary particles. The transition from physics to chemistry is made via the periodic table. The book goes to shif to the planet on which we live. The last major subject is the evolution of the universe starting from the big bang and ending with the origin of the earth